Example of geotechnical monitoring of soil improvement using rigid inclusions under road embankment - Jabłonowski, Adam; Kanty, Piotr; Krasiński, Adam; Sieńko, Rafał; Bednarski, Łukasz; Makowska, Karolina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
The article describes an existing and pioneering measurement system, which can be called a geotechnical monitoring system. This system has string sensors measuring strains, stresses and forces and was installed in concrete columns strengthening weak soil subgrades. Concrete columns using full displacement technology strengthen the ground under the embankment of the expressway No. S7 between Gdańsk and Elbląg in Poland. In terms of geological structure, the area where the measuring columns were made is characterized by the presence of low-bearing, large-thickness organic soils, such as peats and soft plastic silts, and a high groundwater level. The described geotechnical monitoring system consists of a total of eight measurement columns in four test areas. This article is a presentation of the measurement system and the first results of measurements carried out during column load-bearing tests.
Studia Geotechnica et Mechanica, Vol. 47, 2025, nr 3, s. 1-12
Poprzedni tytuł: Studia Geotechnica
Keywords: geotechnika - czasopisma; mechanika - czasopisma; displacement columns; soil improvement; geotechnical monitoring; deformations and stress sensors; dynamometer